The Effect of Lactobacillus crispatus and Lactobacillus rhamnosusCulture Supernatants on Expression of Autophagy Genes and HPV E6 and E7 Oncogenes in The HeLa Cell Line - Motevaseli, Elahe (Cell J, 2016)
OBJECTIVE: The aim of this study was to clarify the mechanism by which lactobacilli exert their cytotoxic effects on cervical cancer cells. In addition, we aimed to evalu- ate the effect of lactobacilli on the expression of human papilloma virus (HPV) onco- genes. MATERIALS AND METHODS: In this experimental study, using quantitative real-time polymer- ase chain reaction (PCR), we analyzed the expression of CASP3 and three autophagy genes [ATG14, BECN1 and alpha 2 catalytic subunit of AMPK (PRKAA2)] along with HPV18 E6 and E7 genes in HeLa cells before and after treatment with Lactobacillus crispatus and Lactobacillus rhamnosus culture supernatants. RESULTS: The expression of CASP3 and autophagy genes in HeLa cells was de- creased after treatment with lactobacilli culture supernatants. However, this de- crease was not significant for PRKAA2 when compared with controls. In addition, expression of HPV E6 was significantly decreased after treatment with lactobacilli culture supernatants. CONCLUSION: Lactobacilli culture supernatants can decrease expression of ATG14 and BECN1 as well as the HPV E6 oncogene. It has been demonstrated that the main changes occurring during cervical carcinogenesis in cell machinery can be reversed by suppression of HPV oncogenes. Therefore, downregulation of HPV E6 by lacto- bacilli may have therapeutic potential for cervical cancer. As the role of autophagy in cancer is complicated, further work is required to clarify the link between downregula- tion of autophagy genes and antiproliferative effects exerted by lactobacilli.